Seabed morphology and shallow sedimentary structure of the Storfjorden and Kveithola trough-mouth fans (North West Barents Sea) - Pedrosa-González, María Teresa; Camerlenghi, Angelo; De Mol, Ben; Urgeles, Roger; Rebesco, Michele; Lucchi, Renata G. (Marine Geology, 2011)
17 pages, 13 figures, 2 tables This study aims to present an overview of the seafloor morphology and shallow sedimentary structure of the Storfjorden and Kveithola Trough Mouth Fans (TMFs) on the northwestern Barents Sea continental margin. Data have been compiled from two International Polar Year (IPY) cruises (SVAIS, of the BIO Hespérides and EGLACOM of the R/V OGS-Explora) that yielded 15,340 km2 of multi-beam bathymetry and 9500 km of sub-bottom seismic profiles. In this area, the continental shelf edge defines three wide and subdued sedimentary lobes forming Storfjorden TMF, one single lobe on Kveithola TMF, and three inter-TMF areas on the continental slope. The two northernmost lobes of Storfjorden TMF (Lobes I and II) are composed by thick (up to 50 m) sequences of glacially derived debris flow deposits interbedded with thin a few metres de-glacial and interglacial deposits. A network of upper slope gullies incises these debris flow deposits as a consequence of subglacial meltwater release at or near the shelf break. Gullies evolve into channels whose morphologic evidence disappears midslope, leaving place to a subdued chevron-like morphological pattern inherited by the preceeding glacial maximum debris flow deposits. A drastic change occurs on the continental slope of Storfjorden TMF Lobe III and Kveithola TMF, where are several translational submarine landslides mostly originated in the upper slope, the majority of which detach at the contact between Middle Weishelian glacigenic debris flows and the overlying acoustically laminated plumites. Dendritic canyon systems only develop in inter-TMF areas. The data suggest that TMF continental slope progradation depends on short-lived episodes of extreme sedimentation during glacial maxima and during the early deglaciation phase, and that an important controlling factor is the mechanism of ice stream retreat from the continental shelf edge. We suggest that the two northern Storfjorden sub-ice streams were composed of thicker and perhaps faster ice ...